Studies in Man and Experimental Animals of a Low Molecular Weight Heparin Fraction - Thomas, D P; Merton, R E; Lewis, W E; Barrowcliffe, T W (Thrombosis and Haemostasis, 1981)
In vitro and in vivo studies were carried out on a commercially prepared low molecular weight heparin fraction. By APTT assay the fraction had a specific activity of half that of unfractionated mucosal heparin, yet retained full potency by anti-Xa assay (both clotting and chromogenic substrate). When administered intravenously to human volunteers, the anti-Xa/APTT ratio remained the same as it was in vitro. However, after subcutaneous injection, the ratio increased and anti-Xa activity could not be fully neutralized ex vivo by PF4. The fraction was as effective as unfractionated heparin in preventing experimental serum-induced thrombosis, suggesting that a heparin fraction with high specific activity by anti-Factor Xa assay compared to APTT activity may be an effective drug for the prophylaxis of venous thrombosis.
Keywords: Heparin; Heparin fraction; Experimental venous thrombosis